Effectiveness of two types of intervention on antibiotic prescribing in respiratory tract infections in Primary Care in Spain. Happy Audit Study - Llor, Carles (Aten Primaria, 2014)
OBJECTIVE: To evaluate the effectiveness of two types of intervention in reducing antibiotic prescribing in respiratory tract infections (RTI). DESIGN: Before–after audit-based study. SETTING: Primary Care centres in Spain. PARTICIPANTS: General practitioners (GPs) registered all patients with RTIs for 15 days in winter 2008 (pre-intervention), and again in winter 2009 (post-intervention). INTERVENTIONS: Intervention activities included meetings, with the presentation and discussion of the results, and several training meetings on RTI guidelines, information brochures for patients, workshops on point-of-care tests – rapid antigen detection tests and C-reactive protein rapid test – and provision of these tests in the clinic. All GPs, with the exception of those in Catalonia, made up the full intervention group (FIG); conversely, Catalan doctors underwent the same intervention, except for the workshop on rapid tests (partial intervention group, PIG). Multilevel logistic regression was performed taking the prescription of antibiotics as the dependent variable. RESULTS: Out of a total of 309 GPs involved in the first register, 281 completed the intervention and the second register (90.9%), of which 210 were assigned to the FIG, and 71 to the PIG. The odds ratio of antibiotic prescribing after the intervention was 0.99 (95% CI: 0.89–1.10) among GPs assigned to PIG, and 0.50 (95% CI: 0.44–0.57, p < 0.001) among those who were allocated to FIG. The reduction in antibiotic prescribing in FIG was more marked in flu infection, common cold, acute pharyngitis, acute tonsillitis, and acute bronchitis. CONCLUSIONS: Active participation of GPs with the performance of point-of-care tests in the clinic is accompanied by a drastic reduction of antibiotic use in RTIs, primarily in infections considered as mainly viral.